Associations of phase angle with platelet-activating factor metabolism and related dietary factors in healthy volunteers - Detopoulou, Paraskevi; Fragopoulou, Elizabeth; Nomikos, Tzortzis; Antonopoulou, Smaragdi (Frontiers in Nutrition, 2023)
Introduction: Phase angle (PA) derives from bioelectrical impedance analysis (BIA). It reflects cell membrane function and decreases in disease. It is affected by inflammation, oxidative stress and diet. Platelet-activating factor (PAF) is a potent inflammatory lipid mediator. Its levels along with the activity of its metabolic enzymes including CDP-choline:1-alkyl-2-acetyl-sn-glycerolcholinephosphotransferase, acetyl-CoA:lyso-PAF-acetyltransferases and PAF-AH/Lp-PLA2 are also related to dietary factors, such as the dietary antioxidant capacity (DAC). The aim of the study was to estimate whether PAF metabolic circuit, and related dietary factors are associated to PA in healthy volunteers.Methods: In healthy subjects, PAF, its metabolic enzymes activity and erythrocyte fatty acids were measured, while desaturases were estimated. Food-frequency questionnaires and recalls were used and food groups, macronutrient intake, MedDietScore and DAC were assessed. Lifestyle and biochemical variables were collected. DXA and BIA measurements were performed.Results: Lp-PLA2 activity was positively associated with PA (rho=0.651, p<0.001, total population; rho=0.780, p<0.001, females), while PAF levels were negatively associated with PA only in men (partial rho= -0.627, p=0.012) and inversely related with DAC. Estimated desaturase 6 was inversely associated with PA (rho=-0.404, p= 0.01, total sample). Moreover, the DAC correlated positively with PA (rho=0.513, p=0.03, women). All correlations were adjusted for age, BMI and sex (if applicable).Conclusions: PA is associated with PAF levels and Lp-PLA2 activity in a gender dependent fashion indicating the involvement of PAF in cell membrane impairment. The relationship of PA with DAC suggests a protective effect of antioxidants on cellular health considering that antioxidants may inhibit PAF generation.